2010
DOI: 10.1177/1049909110366852
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Collaboration: The Voices of Hospice Medical Directors

Abstract: The value of interdisciplinary collaboration is a significant aspect of the palliative care philosophy, as identified by the founder of the modern hospice movement Cecily Saunders. The purpose of this descriptive study was to explore the experiences of hospice medical directors within this collaborative context. Open-ended interviews with 17 hospice medical directors were done and their responses were thematically analyzed. These narratives present a very positive collaborative experience by these medical dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The professional differences found in the subscale are similar to those of previous studies examining perceptions and experiences of interdisciplinary work among hospice professionals. [40][41][42] Job satisfaction was another area where professional discipline showed a significant difference. As a professional discipline, physicians were most happy with their jobs, and social workers reported the least job satisfaction with their job and their work environment.…”
Section: Discussionmentioning
confidence: 99%
“…The professional differences found in the subscale are similar to those of previous studies examining perceptions and experiences of interdisciplinary work among hospice professionals. [40][41][42] Job satisfaction was another area where professional discipline showed a significant difference. As a professional discipline, physicians were most happy with their jobs, and social workers reported the least job satisfaction with their job and their work environment.…”
Section: Discussionmentioning
confidence: 99%
“…The model integrates 4 theories-multidisciplinary theory of collaboration, services integration, role theory, and ecological systems theory-to describe successful team collaboration. 35,39,25 Bronstein's model consists of the following 5 components: interdependence, flexibility, newly created professional activities, collective ownership of goals, and reflection on the collaborative process. 7,35 Interdependence refers to the notion of team members relying on each other in order to achieve shared goals.…”
Section: Interdisciplinary Team Dynamics and Collaborationmentioning
confidence: 99%
“…In addition to mandatory bereavement support, some hospices offer art, massage, or pet therapy. Much research on communication and collaboration has demonstrated the complexity of hospice care the IDT provides (Oliver, Tatum, Kapp, & Wallace, 2010; Oliver, Wittenberg-Lyles, & Day, 2006; Wittenberg-Lyles, Oliver, Demiris, Baldwin, & Regehr, 2008; Wittenberg-Lyles, Oliver, Demiris, & Regehr, 2010). To our knowledge, however, no researchers have specifically explored the setting of hospice care in the United States and its influence on IDT roles and care processes.…”
Section: Roles Of Interdisciplinary Team Membersmentioning
confidence: 99%